Short sleeping duration is associated with a higher risk of asymmetric handgrip strength among older Chinese males: a cross-sectional study evidence from the China health and retirement longitudinal study - Wang, Yilin; Li, Mei; Chen, Xiaoyan (Frontiers in Public Health, 2023)
Objective This study aimed to explore the potential correlation between sleeping duration and the risk of handgrip strength (HGS) asymmetry in older Chinese adults. Methods The data of participants (65+ years of age) were obtained from the first Wave 1 (2011) of the China Health and Retirement Longitudinal Study (CHARLS). Information on sleeping duration during the previous month was collected from self-reports and was divided into three groups: long (>8 h), normal (6–8 h), and short (< 6 h). HGS was computed as the average of two tests per hand and asymmetric HGS was diagnosed when the ratio of average non-dominant to average dominant HGS was greater than 1.1 or less than 0.9. Logistic regression analyses were employed to gauge the relationship between sleeping duration and asymmetric HGS risk. Results In total, 3,174 participants were enrolled in this analysis, of whom 51.54% (1,636/3,174) were male. The proportions of asymmetric HGS were 42.18% in males and 41.87% in females. The sleeping duration (hours) in the asymmetric and non-asymmetric HGS groups were 6 h (5,8) and 7 h (5,8) in males with a significant difference between them (p = 0.015), and 6 h (5,8) and 6 h (5,8) in females with no significant difference (p = 0.415). Compared with non-asymmetric HGS individuals, the proportions of normal, short, and long sleeping duration were 40.4, 47.3, and 37.7% in males with a significant difference (p = 0.023), and 42.4, 40.3, and 43.8% in females with no significant differences (p = 0.685). An adjusted logistic regression analysis model confirmed that short sleeping duration was significantly associated with asymmetric HGS risk among older males (p = 0.048, OR = 1.252, 95%CI:1.002–1.565). Conclusion The results demonstrated that short sleeping duration (<6 h) was a risk factor for increased HGS asymmetry among older Chinese males.